Microbes on the edge of Occam’s razor - Starokadomskyy, Petro (Biol Direct, 2014)
ABSTRACT: Our body harbors hundreds of microbial species and contains many more bacterial than human cells. These microbes are not passive riders but rather a vital component of the organism. The human microbiota affects our health in multiple ways, both positively and negatively. One of the new attractive directions in microbiome biology is the “microbiome-brain axis”. Several groups of researchers have described the ability of the gut microbiota to communicate with the brain and thus modulate human behavior. These limited experimental data became the foundation of the “biomeme hypothesis” of possible microbial origin of some religious rituals that has recently appeared in Biology Direct. Here I propose a critical analysis of this hypothesis. I conclude that there is no evidence of the microbial origin of religious practices but there are strong indications of their psychological and social roots. REVIEWERS: This article was reviewed by Eugene Koonin, Neil R Smalheiser, Etienne Joly.